2014
DOI: 10.1111/j.1540-4781.2014.12063.x
|View full text |Cite
|
Sign up to set email alerts
|

Domesticating the Foreign: Globalization's Effects on the Place/s of Languages

Abstract: Foreign language education is deeply affected by globalization, destabilizing some of the central ideas that have helped form national languages, and, by contrast, foreign languages. This article traces the economic origins of contemporary globalization and the deep communication effects that arise. Migration of peoples, instantaneous communication technologies, and new modes of imagining relationships in the context of vast flows of population, ideas, goods, and communication mean that teachers of different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(31 citation statements)
references
References 35 publications
0
30
0
1
Order By: Relevance
“…In motivation research the changed role of English as a world auxiliary language (Lo Bianco, ) that is indispensable in cross‐cultural communication (Clyne & Sharifian, ) has been evident for some time (Ushioda & Dörnyei, ). A decade ago, in their large‐scale longitudinal study of Hungarian students’ motivation, Dörnyei, Csizér, and Németh () first identified the effects of this shifting status.…”
Section: English In Transformationmentioning
confidence: 99%
“…In motivation research the changed role of English as a world auxiliary language (Lo Bianco, ) that is indispensable in cross‐cultural communication (Clyne & Sharifian, ) has been evident for some time (Ushioda & Dörnyei, ). A decade ago, in their large‐scale longitudinal study of Hungarian students’ motivation, Dörnyei, Csizér, and Németh () first identified the effects of this shifting status.…”
Section: English In Transformationmentioning
confidence: 99%
“…En China se estudia las prácticas lingüísticas de los académicos multilingües en las publicaciones académicas, a la vez que el gobierno amplía la educación multilingüe en la enseñanza superior (ZHENG; GUO, 2019). Sin embargo, al contrario, ocurre en Inglaterra, donde los estudios se centran, entre otros aspectos, en el deficiente historial británico para el aprendizaje de idiomas por el inglés global, ya que las razones utilitarias para aprender idiomas distintos al inglés se ven minadas (LANVERS, 2017;LO BIANCO, 2014).…”
Section: Introductionunclassified
“…Furthermore, in some Member States, English has acquired the status of ‘basic skill’; that is, an academic subject to be mastered to high levels of proficiency, with many more hours devoted to its learning than to other FLs (European Commission, ). This attribution to English of the status of additional rather than foreign language is increasingly common in other parts of the world (Lo Bianco, ; see also Graddol, ). As a result, proficiency in the new lingua franca rather than multilingualism has become an essential commodity in the global marketplace (Dewaele, ).…”
Section: Profile Of the Foreign Language Classroom In The Mlj: Surveymentioning
confidence: 97%
“…We acknowledge that the distinctions between ‘second’ and ‘foreign’ are increasingly blurred (Kramsch, ; Spolsky, ), notably in the case of a lingua franca language such as English (Cogo, ; Kachru, ; Nayar, ; Swan, ; see also Widdowson, ) or in the case of a commodified language, such as Russian has become in Europe (Pavlenko, ) . We also acknowledge the changes brought about by globalization and population mobility to the concept of ‘foreign’ itself when real‐time instantaneous communication has altered the significance of geographical distribution of languages and their availability (Lo Bianco, ). However, the terms are used by the MLJ in the description of its editorial mission, and they also figure as keywords for articles published in the journal.…”
Section: Definitions and Scopementioning
confidence: 99%
See 1 more Smart Citation